Regulation of hepatic glutamine metabolism by miR-122 - Dipanwita Sengupta; Teresa Cassel; Kun-yu Teng; Mona Aljuhani; Vivek K. Chowdhary; Peng Hu; Xiaoli Zhang; Teresa W.-M. Fan; Kalpana Ghoshal (Elsevier, 2020)
Objective: It is well established that the liver-specific miR-122, a bona fide tumor suppressor, plays a critical role in lipid homeostasis. However, its role, if any, in amino acid metabolism has not been explored. Since glutamine (Gln) is a critical energy and anaplerotic source for mammalian cells, we assessed Gln metabolism in control wild type (WT) mice and miR-122 knockout (KO) mice by stable isotope resolved metabolomics (SIRM) studies. Methods: Six-to eight-week-old WT and KO mice and 12- to 15-month-old liver tumor-bearing mice were injected with [U-13C5,15N2]-L-Gln, and polar metabolites from the liver tissues were analyzed by nuclear magnetic resonance (NMR) imaging and ion chromatography-mass spectrometry (IC-MS). Gln-metabolism was also assessed in a Gln-dependent hepatocellular carcinoma (HCC) cell line (EC4). Expressions of glutaminases (Gls and Gls2) were analyzed in mouse livers and human primary HCC samples. Results: The results showed that loss of miR-122 promoted glutaminolysis but suppressed gluconeogenesis in mouse livers as evident from the buildup of 13C- and/or 15N-Glu and decrease in glucose-6-phosphate (G6P) levels, respectively, in KO livers. Enhanced glutaminolysis is consistent with the upregulation of expressions of Gls (kidney-type glutaminase) and Slc1a5, a neutral amino acid transporter in KO livers. Both Gls and Slc1a5 were confirmed as direct miR-122 targets by the respective 3'-UTR-driven luciferase assays. Importantly, expressions of Gls and Slc1a5 as well as glutaminase activity were suppressed in a Gln-dependent HCC (EC4) cell line transfected with miR-122 mimic that resulted in decreased 13C-Gln, 13C-á-ketoglutarate, 13C-isocitrate, and 13C-citrate levels. In contrast, 13C-phosphoenolpyruvate and 13C-G6P levels were elevated in cells expressing ectopic miR-122, suggesting enhanced gluconeogenesis. Finally, The Cancer Genome Atlas-Liver Hepatocellular Carcinoma (TCGA-LIHC) database analysis showed that expression of GLS is negatively correlated with miR-122 in primary human HCCs, and the upregulation of GLS RNA is associated with higher tumor grade. More importantly, patients with higher expressions of GLS or SLC1A5 in tumors exhibited poor survival compared with those expressing lower levels of these proteins. Conclusions: Collectively, these results show that miR-122 modulates Gln metabolism both in vitro and in vivo, implicating the therapeutic potential of miR-122 in HCCs that exhibit relatively high GLS levels. Keywords: Glutaminase, Glutaminolysis, Gluconeogenesis, Krebs cycle, miRNA-122, miR-122, SIRM, Slc1a5